A novel smaller β‐defensin‐derived peptide is active against multidrug‐resistant bacterial strains. Issue 12 (24th November 2021) - Colicchio, Roberta; Nigro, Ersilia; Colavita, Irene; Pagliuca, Chiara; Di Maro, Salvatore; Tomassi, Stefano; Scaglione, Elena; Carbone, Fortunata; Carriero, Maria Vincenza; Matarese, Giuseppe; Daniele, Aurora; Cosconati, Sandro; et al.
Abstract: Antibiotic resistance is becoming a severe obstacle in the fight against acute and chronic infectious diseases that accompany most degenerative illnesses from neoplasia to osteo‐arthritis and obesity. Currently, the race is on to identify pharmaceutical molecules or combinations of molecules able to prevent or reduce the insurgence and/or progression of infectivity. Attempts to substitute antibiotics with antimicrobial peptides have, thus far, met with little success against multidrug‐resistant (MDR) bacterial strains. During the last decade, we designed and studied the activity and features of human β‐defensin analogs, which are salt‐resistant, and hence active also under high salt concentrations as, for instance, in cystic fibrosis. Herein, we describe the design, synthesis, and major features of a new 21 aa long molecule, peptide γ2. The latter derives from the γ‐core of the β‐defensin natural molecules, a small fragment of these molecules still bearing high antibacterial activity. We found that peptide γ2, which contains only one disulphide bond, recapitulates most of the biological properties of natural human β‐defensins and can also counteract both Gram‐positive and Gram‐negative MDR bacterial strains and biofilm formation. Moreover, it has great stability in human serum thereby enhancing its antibacterial presence and activity without cytotoxicity in human cells. In conclusion, peptide γ2 is a promising new weapon also in the battle against intractable infectious diseases.